Effect of elevated C02 on bacterial growth efficiency - Nurul Fitrah, M.; Chui, W.B.; Choon, W.L. (2012)
The rise of CO2 levels in oceanic surface waters may have potential effect on marine bacteria although experimental results related to the effects of CO2 on marine microbes are rather inconsistent and at times conflicting. In the present study, we investigated the effect of elevated CO2 in seawater on bacterial production (BP), bacterial respiration (BR) and bacterial growth efficiency (BGE) at two different locations which are Port Klang and Port Dickson. A total of six sets of experiment were conducted for each location with different concentrations of CO2 ranging from 2.95 to 99.35 urnol kg·l. Estimation of bacterial production and bacterial respiration obtained ranged between 0.06 to I 04 I!M C h·1 and 0.18 to 2.72 I!M O2 n', respectively. Bacterial growth efficiency was calculated as bacterial production/. (bacterial production + respiration) ranged from 0.08 to 0.54. CO2 and bacterial growth efficiency were significantly correlated (r= 0.277, df= 52, P < 0.05). The results from this experiment suggest that an increase in atmospheric CO2 might affect BGE, and may have implications towards understanding the ocean carbon flux.